Platelet Function in Acute Myocardial Infarction Patients Compared with Controls - O'Brien, John R; Etherington, Michael D; Shuttleworth, Robert D; Calwell, William H (Thrombosis and Haemostasis, 1980)
A considerable number of tests were carried out comparing 33 patients with acute myocardial infarction (MI), 13 patients with chest pain (CP) and 47 controls. There was some evidence that the plasma platelet factor 4 (PF4) was different in the three groups. The heparin neutralizing activity (HNA) of platelet poor plasma was increased in the MI patients relative to the controls and the intra-platelet HNA was decreased. Malondialdehyde (MDA) formation by platelets maximally stimulated by thrombin was decreased in MI whilst the plasma 5-hydroxyindoles (5HIs) in MI was greatly increased. The acute phase proteins α1 acid glycoprotein and fibrinogen were significantly raised in MI. The results in the CP group were intermediate between the MI and the controls. These findings define more precisely the changes in acute MI and are relevant to the concept of exhausted platelets.
Keywords: Myocardial infarct; Heparin neutralizing activity; Platelet factor 4; Serotonin; Exhausted platelets